Scramble Learning Model on Students' Collaboration Skills in Civic Education Subjects in Class V of SDN 06663 Tegal Sari Mandala II - Salsabila, Nadya (Berpusi Publishing, 2024)
The aim of this research is to see whether or not there is a comparison of the results of students' collaboration abilities after treatment using the scramble learning model and before using the scramble learning model. This type of research is a Pre-Experimental Design experiment, the research sample was taken from class V with a total of 20 students. The research results show differences in learning outcomes between students who use the scramble learning model and use conventional media. The results of the data analysis obtained showed a sig value. < 0.05, namely 0.000 < 0.05, then the hypothesis shows that there is a significant influence on the average questionnaire score before and after treatment.